2021
DOI: 10.12669/pjms.37.4.3476
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Risk of Spontaneous Bacterial Peritonitisdue to increase use of Proton Pump Inhibitors among cirrhotic patients with ascites

Abstract: Objectives: The current study aimed to determine the Spontaneous Bacterial Peritonitis (SBP) risk due to increased use of Proton Pump Inhibitors (PPIs) among cirrhotic patients with ascites. Methods: This retrospective case-control study was conducted at Chandka Medical College & Hospital, Larkana from March 2013 to February 2014, involving 215 cirrhotic patients with ascites. Paracentesis was performed to distinguish cirrhotic patients with SBP and Polymorphonuclear Neutrophil (PMN) count ≥ 250 neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Similarly, a prospective study has found that in rats with cirrhosis induced by common bile duct ligation, the improvement of hyperhomocysteinemia can substantially reduce both portal pressure and the risk of occurrence of CLD-related adverse events including HE and gastrointestinal bleeding [ 17 , 18 ]. An additional study on SBP in CLD victims has found interrelationship between serum homocysteine and SBP, and the level of serum homocysteine serves as a predictor for CLD-SBP [ 19 , 20 ]. Recently, high concentrations of bile acids have been found in the cerebrospinal fluid of patients with liver cirrhosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a prospective study has found that in rats with cirrhosis induced by common bile duct ligation, the improvement of hyperhomocysteinemia can substantially reduce both portal pressure and the risk of occurrence of CLD-related adverse events including HE and gastrointestinal bleeding [ 17 , 18 ]. An additional study on SBP in CLD victims has found interrelationship between serum homocysteine and SBP, and the level of serum homocysteine serves as a predictor for CLD-SBP [ 19 , 20 ]. Recently, high concentrations of bile acids have been found in the cerebrospinal fluid of patients with liver cirrhosis [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPI should be administered to patients who will benefit from its use. In elderly patients with severe liver injury, particularly those with ascites in LC, PPI treatment should be avoided or administered with caution to lower the risk of SBP (75)(76)(77).…”
Section: Clinical Interventionmentioning
confidence: 99%